Investigation of disruption management practices and environmental impact on Malaysian automotive supply chains: a case study approach - Noraida Azura Md Darom; Hawa Hishamuddin; Rizauddin Ramli; Zulkifli Mohd Nopiah; Ruhul A Sarker (Penerbit Universiti Kebangsaan Malaysia, 2020)
Much focus on managing a supply chain in the event of disruption has been on the financial consequences and the service level impact on the customers. The negative impact caused by the disruption could influence a company’s profit and market share. Nonetheless, the importance of the environmental impact consideration in the supply chain disruption management has not been emphasised in the existing literature despite research findings that highlight the impact of some resilient supply chain practices on its environmental sustainability. This paper aims to assess the relationship between supply chain mitigation and recovery practices and its environmental impact. To achieve this objective, a case study was employed where semi-structured interviews were conducted at selected automotive companies in Malaysia. The results show that most disruption mitigation and recovery practices of a supply chain have a medium impact on its environmental performance. In particular, the production process during supply disruption recovery has the highest influence on environmental performance in the form of waste generation and use of energy. The results of this study can be used by supply chain managers to focus their efforts in the right direction in order to achieve cost objectives, service levels and environmental goals during the management of disruptions.